Ethnic and Cultural Diversity in Southeast Sulawesi: A Socio-Cultural Analysis from a Contemporary Perspective - Milda Yanti; Mikyal Hardiyati (Journal of Contemporary Islamic Primary Education, 2025)
This study aims to analyze the diversity of ethnic groups and cultures in Southeast Sulawesi and how this diversity affects the social, economic, and political dynamics of local communities. Southeast Sulawesi Province is a region rich in ethnic diversity, with major ethnic groups such as Tolaki, Muna, Buton, Moronene, Bugis, and Bajo. Through a qualitative approach with ethnographic methods and literature studies, this study explores how ethnic and cultural diversity interact in the context of social change and globalization. The results of the study indicate that the wisdom of the local community of Southeast Sulawesi has enabled the formation of social harmony amidst diversity, despite challenges in the context of modernization and economic development. This study also identifies efforts to preserve culture amidst the social transformation that is occurring, as well as the role of government and society in maintaining local cultural identity as an asset for regional development.